1996
DOI: 10.1016/s0022-5347(01)65472-7
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Trauma: Potential Impact on Reproductive Function

Abstract: There was definite evidence of subfertility as assessed by abnormal semen analyses and atrophic testes following testicular trauma. However, the subfertility did not appear to be immune mediated nor did the patients present with infertility. Since only 1 patient had severely compromised fertility according to semen analysis we conclude that early repair can help preserve hormonal function as well as fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 14 publications
0
26
0
5
Order By: Relevance
“…Followup studies show no detrimental effect of testicular salvage on subsequent fertility [2,22]. However, when massive injury is sustained, resulting in scant viable testicular parenchyma, orchidectomy should follow (LOE 3, Fig.…”
Section: Managementmentioning
confidence: 99%
“…Followup studies show no detrimental effect of testicular salvage on subsequent fertility [2,22]. However, when massive injury is sustained, resulting in scant viable testicular parenchyma, orchidectomy should follow (LOE 3, Fig.…”
Section: Managementmentioning
confidence: 99%
“…20 Several studies reported that heavy metal toxicity in men impaired spermatogenesis and decreased sperm counts. [21][22][23][24] Inorganic lead can disturb the pro-oxidant and antioxidant balance and cause oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings suggest a possible effect of the injury on fertility. Interestingly, one patient had infertility treatment for the presence of antisperm antibodies, signifying that a testicular or other reproductive tract injury might have occurred at the time of the PFUDD injury [5]. Another man with abnormally low sperm counts was being treated for an ongoing recto-cutaneous fistula that developed after a rectal injury that occurred at the time of his pelvic fracture.…”
Section: Discussionmentioning
confidence: 99%